Assessment of Surface Roughness of Nickel Free Orthodontic Brackets and Archwires (An In Vitro Comparative Study) - Dina Hamid Obaid1 , Dhiaa J. Nasir AL-Dabagh2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Orthodontic appliances may cause many side effects, one of these is inducing nickelhypersensitivity as a result of nickel content of these appliances, therefore, it is essential to choose abracket and archwire that are nickel free and have a better surface characteristic to be more efficient for theorthodontic treatment. Hence, the aim of this study is to assess the surface roughness of nickel free metalbrackets and archwires.Materials and Method: Two types of nickel free brackets were used (Ni free SS brackets and Co-Crbrackets), a 0.022-inch slot, and three types of nickel free archwires of 0.018 x 0.025 inch were used (Nifree SS, TMA, and rhodium coated SS archwires). These brackets and wires were examined for their surfaceroughness by the atomic force microscope (AFM) using the roughness average parameter (Ra). For thestatistical analysis Mann-Whitney U test was used for the comparison between the brackets, while, KruskalWallis test was used for the comparison among the archwires (non-parametric tests) at level of significant0.05, by using SPSS software version 23.Results: Regarding the brackets, there was no statistically significant difference between the surfaceroughness of the two brackets types, while, regarding the archwires, there was a statistically significantdifference between the as received archwires; as the nickel free stainless steel wires had the lowest value ofroughness average, while, the TMA wires had the highest value of roughness average.Conclusions: Ni free SS wires considered the best choice as a working wire for patients with nickel allergy